Resilient or residual? From the wage earners' welfare state to market conformity in New Zealand - Peter Starke (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2005)
Contemporary research has frequently stressed the resilience of welfare states facing internal and external problem pressure or ideologically motivated attacks. Theoretical explanations of welfare state change have in part been eclipsed by explanations of its remarkable stability. But does the resilience thesis hold? Taking the case of New Zea-land, this paper demonstrates that under certain conditions major transformation is pos-sible. Since 1975, New Zealand has changed from being a `wage earners welfare state to having only a residual system of social protection. Adopting a qualitative approach, the paper describes the process of welfare state retrenchment through different phases and discusses what economic and political-institutional conditions account for the un-usually large extent of cutbacks. Quantitative data confirm the pattern of retrenchment with the most extensive cutbacks taking place in the early 1990s under conservative rule. This pattern does not, however, bear out the expectation of `blame avoidance behaviour, as assumed by previous research. Despite the unpopularity of retrenchment, governments in New Zealand frequently used the opportunities provided by the central-ised political system to push through highly visible reforms.
Keywords: 330; Sozialreform; Haushaltskonsolidierung; Soziale Mindestsicherung; Marktwirtschaft; Neuseeland